Интерпретация понятий сирота и сиротство в английских и узбекских пословицах - Safarova, Zilola (Центр Научных Публикаций (buxdu.uz), 2021)
One of the ancient genres of folklore proverbs are the conclusions drawn from the experiences of our ancestors over the centuries